The Mysterious One-Third Stress Increase - Ellifritt, Duane S. (Engineering Journal, 1977)
It has been customary throughout three or four generations of structural engineers to use a higher allowable stress when considering the stresses produced by wind in a structure. Much later, the same provision was allowed for earthquake related stresses. Recently, this increase has come under attack from many quarters and there has been some confusion as to what was the rationale for permitting this increase in the first place. Just what physical phenomenon is it supposed to account for? When was it first introduced and why? If it was valid at the time of its origin, is it still valid today? The criticism has come from various sources. For example, engineers on the west coast have been lobbying to get rid of the provision for several years, primarily for earthquakes, but wind usually gets caught up in the fervor. Each year some building official proposes to the Uniform Building Code that the increase be abolished for both earthquake and wind. Each year the proposal is defeated. Since the earthquake provision came later and was probably borrowed from the wind provision, let us remove earthquakes from consideration here and investigate the validity of the permitted stress increase for wind only.